The Effect of Disability on Employment Allowing for Work Incapacity - Owen O'Donnell (University of Kent, Department of Economics, 1998)
Previous modelling of the impact of disability on employment has failed to allow for a direct effect rendering some individuals capable of work. A model in which both a capacity and a desire for work are necessary conditions for employment is estimated from a sample of British disabled men. Recognition that individuals may be incapable of work helps identify work capacity and leads to a test for errors in reported capacity data. The capacity for work condition is found to be relevant and failure to allow for it results in overestimation of the wage elasticity of employment. The accuracy of self-reported capacity information is rejected.
Keywords: I12; J22; 330; Disability; Work Capacity; Employment; Labour Supply; Partial Observability; Reporting Errors; Behinderte Arbeitskräfte; Arbeitsangebot; Leistungsmotivation; Erwerbstätigkeit; Schätzung; Großbritannien